The design of solar powered refrigerator / Aboo Bakar Merican Ismail Merican and Mohd. Hashim Abd. Rahman - Ismail Merican, Aboo Bakar Merican; Abd. Rahman, Mohd. Hashim (1982)
Solar refrigeration is a means of using power a refrigeration system. This energy can be transform in two ways, indirectly or by direct conversion. First, solar energy can be converted to electrical energy follow by Mechanical energy and thence operate a conventional vapour compression refrigerator. Secondly solar energy can be used to heat the working fluid in a vapour absorption refrigerator, for this case it can be considered as direct conversion. Indirect conversion has a low efficiency and high cost of fabrication as the first case. The absorption refrigeration system can be classified into two types, intermittent and continuous. The intermittent refrigeration cycle has two major operations, regeneration and refrigeration. Regeneration is the process of heating the refrigeration - absorbent fluid to drive off the refrigerant absorbent is allowed to cool and refrigeration takes place when the liquid refrigerant is reabsorbed by the absorbent.